AlN polycrystalline material with skeleton structure and sintering device thereof
Through the AlN polycrystalline material and sintering device with a skeleton structure, the problems of low growth rate and uneven surface of large-size AlN crystals are solved, and more efficient crystal growth and better surface quality are achieved.
Patent Information
- Application Number
- CN202510546114.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-28
- Publication Date
- 2025-08-05
AI Technical Summary
When large-size AlN crystals grow, the crystal growth rate is low and the crystal surface growth rate is uneven.
The AlN polycrystalline material adopting a skeleton structure includes a plurality of cylindrical material pieces, each of which has multiple through holes in the axial direction, and the small pieces are stacked in communication with the through holes, and sintered using a specific sintering device.
It improves the crystal growth rate, improves the crystal surface quality, and provides more process adjustment space, optimizing the crystal growth process.
Smart Images

Figure CN120425458A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of crystal growth technology, and more specifically, relates to an AlN polycrystalline material with a skeleton structure and a sintering device thereof. Background Art
[0002] Aluminum nitride single crystal has an ultra-wide band gap (6.2 eV), a high breakdown field strength (15 MV·cm -1 ), high thermal conductivity (3.4 W·cm -1 ·K -1 ), high sound velocity (>5.5 km / s), high temperature resistance, strong radiation resistance, acid and alkali resistance, and other excellent properties make it ideal for the fabrication of deep ultraviolet LEDs, LDs, RF power devices, and surface / bulk acoustic wave devices. Currently, physical vapor transport (PVT) is the most successful method for growing AlN single crystal substrates. This method has been used internationally to grow 4-inch AlN crystals, with high-quality AlN crystals measuring 2 inches.
[0003] The basic growth principle of AlN crystals prepared by PVT method is that AlN source sublimates at high temperature (>2000℃) in high temperature nitrogen environment and deposits AlN crystals at lower temperature. To realize the commercial production of AlN single crystals by this method, it is necessary to obtain AlN crystals of larger size (≥4 inches) while ensuring the crystallization quality of the crystals. Comparing the simulation of 1-inch and 4-inch AlN crystal growth, it can be seen that the growth rate of the 1-inch center area can reach a maximum of 180 μm / h. Figure 7 As shown in Figure 2, the growth rate in the 4-inch central area dropped to 109 μm / h. Figure 8 As shown; at the same time, in the experiment, under the same process of the same equipment, the growth rate of 1-inch crystal can reach 150un / h, while the growth rate of 4-inch crystal drops to 80un / h, which is the same trend as the simulation results. The decrease in crystal growth rate is very likely to cause more intrinsic defects in the crystal; it also increases the cost of crystal growth. Therefore, in the research and development of large-scale AlN crystal growth and industrial production, improving the crystal growth rate is a major challenge for large-scale AlN crystal growth. According to the thermodynamics of crystal growth, the crystal growth rate , where T is the growth temperature, P is the growth pressure, and ΔT is the temperature gradient. According to the formula, increasing the growth temperature, increasing the temperature gradient, and reducing the pressure can increase the crystal growth rate. In 2020, Jin Lei published an article entitled "Research on the Growth Behavior of AlN Single Crystals" in the Journal of Synthetic Crystals, Volume 49, Issue 11. It can be seen that AlN crystals have different growth habits and growth advantages under different growth processes; afterwards, Qin Zuoyan published "Research on Regulation of AlN Crystal Growth Mode" in Volume 53, Issue 9 of the journal in 2024. It can be seen that the most suitable growth temperature for AlN crystals is 2250°C. It can be seen that the thermodynamic process window for AlN crystal growth is very small and has reached the limit of regulation. Therefore, to increase the growth rate of the crystal, it is necessary to increase the sublimation rate of the material and its transmission rate. The gas phase material in the central area of the traditional material is in a highly supersaturated state, and there is a lack of transmission channels, resulting in low utilization of the material center. The fastest sublimation part is the surface of the material, mainly the side and upper surface, such as Figure 6 As shown. As the crystal size increases, the crucible diameter increases, the volume of unfilled material in the crucible increases, the material volume increases with the quadratic exponential of the size, and the sublimation area on the side of the material increases in proportion to the size. Therefore, the larger the size, the lower the sublimation rate of the material. The growth rate of the crystal also decreases. Secondly, the central area of the material is heated worse as the size increases, the temperature decreases, and the sublimation amount also decreases. According to the research of "Research on Regulation of AlN Crystal Growth Mode", the sublimation rate of the material surface is fast, which leads to uneven supersaturation on the crystal surface. The growth rate of the crystal surface is low in the center and high at the edge. The iterative growth of high-quality AlN crystals cannot be achieved on the crystal surface. According to the simulation results, hollow materials are only suitable for the preparation of smaller-sized AlN crystals, and for larger sizes, there is still the phenomenon of uneven growth rate on the crystal surface.
[0004] Aiming at the problem that the growth rate of large-sized AlN crystals is low and the growth rate on the surface of the crystals is uneven, an AlN polycrystalline material with a skeleton structure and a sintering device thereof were invented. Summary of the Invention
[0005] The purpose of the embodiments of the present application is to provide an AlN polycrystalline material with a skeleton structure and a sintering device thereof, which solves the problems of low crystal growth rate and uneven crystal surface growth rate when growing large-sized AlN crystals.
[0006] To achieve the above-mentioned purpose, the technical solution adopted in this application is: an AlN polycrystalline material with a skeleton structure, comprising: A plurality of cylindrical material blocks, each of which has a plurality of through holes formed in the axial direction; Furthermore, a plurality of cylindrical material blocks are stacked, and the through holes of the connected cylindrical material blocks are all connected.
[0007] Preferably, the through holes are of any shape, and the number of the through holes is greater than or equal to three.
[0008] Preferably, the radial cross-sectional area of the through hole is greater than or equal to 20 mm 2 .
[0009] Preferably, the through hole is arranged at an angle to the radial cross section of the cylindrical material block.
[0010] Preferably, the angle range is set between 45° and 90°, and the directions of the through holes are all in the same direction.
[0011] Preferably, when the angle is 90°, the connected cylindrical material pieces are stacked in an offset manner using the through holes.
[0012] Preferably, when the angle is not 90°, the connected cylindrical material pieces are stacked with their upper and lower surfaces reversed, so that the through holes form an "S"-shaped channel in the material.
[0013] A sintering device for sintering the cylindrical material block according to claim 7, comprising: a crucible bottom, a plurality of rods protruding from the crucible bottom, the rods being adapted to fit within the through holes; A crucible wall is concentrically placed on the crucible bottom, and the thickness of the crucible wall is 1 to 3 mm; a crucible cover, concentrically placed on the crucible wall, wherein the diameter of the crucible cover is larger than the diameter of the crucible wall, and the diameter of the crucible cover is equal to the diameter of the crucible bottom; The inner side surface of the crucible cover abuts against the rod body.
[0014] Preferably, the crucible bottom and the rod body of the sintering device are both made of tungsten material.
[0015] Preferably, the crucible bottom and the crucible cover of the sintering device are both provided with right-angle chamfers, and the right-angle chamfers are used for mounting the crucible wall.
[0016] The beneficial effects of the AlN polycrystalline material with a skeleton structure and the sintering device thereof provided in this application are: The AlN polycrystalline material of a skeleton structure of the present application is formed by multiple cylindrical material blocks, each of which has multiple through holes formed in the axial direction; and multiple cylindrical material blocks are stacked, and the through holes of the connected cylindrical material blocks are all connected, showing obvious advantages in increasing the growth rate, improving the crystal surface quality and providing process adjustment space. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments or descriptions of the prior art. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.
[0018] Figure 1 A schematic diagram of the three-dimensional structure of a cylindrical material block provided in an embodiment of the present application; Figure 2 A schematic diagram of the three-dimensional structure of a sintering device provided in an embodiment of the present application; Figure 3 A schematic structural diagram of the crucible bottom provided in an embodiment of the present application; Figure 4 Schematic diagram of the gas phase material transmission state structure of AlN polycrystalline material with a skeleton structure when the angle between the through hole and the radial cross section of the cylindrical material block provided in the embodiment of the present application is 90° during sublimation; Figure 5 A schematic diagram of the gas phase material transmission state during sublimation of an AlN polycrystalline material with a skeleton structure is provided for the embodiment of the present application when the angle between the through hole and the radial cross section of the cylindrical material block is not 90°; Figure 6 This is a schematic diagram of the gas phase material transmission state during the sublimation of traditional columnar materials; Figure 7 Schematic diagram of the surface growth rate of a 1-inch AlN crystal; Figure 8 Schematic diagram of the surface growth rate of a 4-inch AlN crystal.
[0019] Among them, the reference numerals in the figures are: 1. Small cylindrical pieces of material; 2. Through hole; 3. Crucible cover; 4. Crucible wall; 5. Crucible bottom; 6. Rod; 7. Right-angle chamfer. DETAILED DESCRIPTION
[0020] In order to make the technical problems, technical solutions and beneficial effects to be solved by this application more clearly understood, this application is further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain this application and are not intended to limit this application.
[0021] It should be noted that when an element is referred to as being “fixed on” or “disposed on” another element, it may be directly on the other element or indirectly on the other element. When an element is referred to as being “connected to” another element, it may be directly connected to the other element or indirectly connected to the other element.
[0022] It should be understood that the terms "length", "width", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship, are based on the orientation or position relationship shown in the accompanying drawings, and are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on this application.
[0023] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of the technical features being referred to. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. Throughout the description of this application, "plurality" means two or more, unless otherwise specifically defined.
[0024] Please also refer to Figures 1 to 5 , an AlN polycrystalline material with a skeleton structure and a sintering device thereof provided in an embodiment of the present application are now described.
[0025] The AlN polycrystalline material of the skeleton structure has a diameter of 40 to 260 mm and a total height greater than or equal to 50 mm. The polycrystalline material comprises: a plurality of cylindrical material blocks 1, the diameter of the cylindrical material block 1 being equal to the diameter of the polycrystalline material and the height being 15 to 50 mm. Each of the cylindrical material blocks 1 is formed with a plurality of through holes 2 in the axial direction. The through holes 2 are of any shape and the radial cross-sectional area of the through holes 2 is greater than or equal to 20 mm. 2 , the number of the through holes 2 is greater than or equal to three; and a plurality of the cylindrical material blocks 1 are stacked, the number of the cylindrical material blocks 1 is greater than or equal to two, and the through holes 2 of the connected cylindrical material blocks 1 are all connected.
[0026] In a preferred embodiment, the through-holes 2 are arranged at an angle relative to the radial cross-section of the cylindrical material pieces 1. The angle is greater than or equal to 45° and less than or equal to 90°, and the through-holes 2 are all oriented in the same direction. When the angle is 90°, the connected cylindrical material pieces 1 are stacked with the through-holes 2 staggered. When the angle is not 90°, the connected cylindrical material pieces 1 are stacked with their upper and lower surfaces reversed, forming an "S"-shaped channel in the material with the through-holes 2.
[0027] The present invention increases the sublimation surface area of the raw material by preparing the skeleton structure material to improve the sublimation amount of the material; at the same time, from the perspective of dynamics, it greatly increases the transmission channel of the gas phase material and increases the sublimation amount of the central area of the material. Figure 4 and 5As shown. Under the process conditions without changing the thermodynamics, the sublimation rate of the raw materials is increased, and the growth rate of the crystal is improved. The raw materials with a skeleton structure realize the uniform sublimation of the whole material, and the uneven supersaturation of the crystal surface is changed. At the same time, the skeleton structure material is also conducive to alleviating the unstable growth caused by the rapid change of the surface area of the traditional material structure during the growth process. By controlling the number and size of the through holes 2 of the cylindrical material block 1, the local growth rate of the crystal surface can be controlled. When the AlN crystal grows, it is a temperature field with a positive temperature gradient. The temperature of the bottom of the crucible 5 is higher than the temperature of the seed crystal area. At the same time, at high temperatures, heat transfer is mainly through radiation heat transfer. By controlling the angle of the stacking of the cylindrical material block 1 and the inclination angle of the through hole 2 of the cylindrical material block 1 to the surface, it is avoided that the through hole 2 of the cylindrical material block 1 causes the heat of the bottom of the crucible 5 to be directly radiated to the seed crystal, resulting in uneven temperature of the seed crystal surface, affecting the growth of the crystal, especially in the nucleation stage at the initial stage of crystal growth.
[0028] A sintering device for sintering the cylindrical material block 1, comprising: a crucible bottom 5, a plurality of rods 6 protruding from the crucible bottom 5, the rods 6 being arranged at an angle to the crucible bottom 5, the angle being greater than or equal to 45° and less than or equal to 90°, the rods 6 being adapted to the through hole 2, the rods 6 being connected to the crucible bottom 5 by integral molding or welding; a crucible wall 4, the crucible wall 4 being concentrically placed on the crucible bottom 5, the thickness of the crucible wall 4 being 1 to 3 mm; the height of the crucible wall 4 is adapted to the height of the cylindrical material piece 1, and the crucible wall 4 and the crucible bottom 5 are designed to be separated. When the rod body 6 is not perpendicular to the crucible bottom 5, the cylindrical material piece 1 can also be taken out smoothly; the crucible cover 3, the crucible cover 3 is concentrically placed on the crucible wall 4, and the diameter of the crucible cover 3 is greater than the diameter of the crucible wall 4, and the diameter of the crucible cover 3 is equal to the diameter of the crucible bottom 5; the inner side surface of the crucible cover 3 abuts against the end of the rod body 6 away from the crucible bottom 5.
[0029] As a preferred embodiment, the crucible bottom 5 and rod 6 of the sintering device are both made of tungsten. Tungsten offers significant advantages, including a high melting point, corrosion resistance, thermal stability, high density, and hardness. It also resists reaction with AlN and N2 at high temperatures. Raw material sintering occurs under a positive temperature gradient, with the crucible bottom 5 at the highest temperature. The integrated structure of the tungsten rod 6 and crucible bottom 5 ensures heat conduction, maintaining a high temperature within the tungsten rod 6 and preventing AlN deposition on the rod 6, which could cause adhesion between the rod 6 and the raw material and prevent removal.
[0030] As a preferred embodiment, the crucible bottom 5 and the crucible cover 3 of the sintering device are both provided with a right-angle chamfer 7, the diameter of the right-angle chamfer 7 is smaller than the inner diameter of the crucible wall 4, and the right-angle chamfer 7 is used to install the crucible wall 4. The right-angle chamfer 7 also has the function of increasing the strength of the crucible cover 3 or the crucible bottom 5, facilitating cleaning, and reducing stress concentration.
[0031] Here are a few comparative experiments: Experiment 1: In this experiment, 4-inch AlN crystals were grown using ordinary cylindrical raw materials at a growth temperature of 2200°C, a growth atmosphere of 99.999% nitrogen, a growth pressure of 600 mbar, and a growth time of 60 h. The specific crystal growth crucible apparatus is as follows: Figure 6 As shown in Figure 2, after the crystal growth is completed, the crucible cooling rate is 20 ℃ / h.
[0032] The AlN crystal grown in this embodiment has an overall growth rate of 50 μm / h, and the overall shape of the crystal is high at the edge and low in the center, with a height difference of about 1 mm. Experiment 2: This embodiment differs from Experiment 1 in that the raw material used is a columnar material with a central opening of 30 mm, and the rest of the process is the same.
[0033] The AlN crystal grown in this embodiment has an overall growth rate of 60 um / h. The crystal surface is W-shaped in radius. At the same time, the temperature in the central region is too high due to bottom radiation, resulting in a low growth rate.
[0034] Experiment 3: This embodiment differs from Experiment 1 in that the raw material used is a cylindrical material, and multiple vertical through holes 2 are evenly distributed in the raw material. The number of through holes 2 is 25, and the diameter is 10 mm. The rest of the process is the same.
[0035] The AlN crystal grown in this embodiment has an overall growth rate of 100 um / h, and a concave phenomenon exists in the area of the crystal surface corresponding to the material through hole 2 .
[0036] Experiment 4: This embodiment differs from Experiment 3 in that the raw material used is a skeleton structure material, consisting of two cylindrical material blocks 1. The number and diameter of the through holes 2 are the same as those in Example 3. The through holes 2 of the cylindrical material blocks 1 are all offset by half of the hole, and the rest of the process is the same.
[0037] The AlN crystal grown in this embodiment has an overall growth rate of 90 um / h, and the concave state of the region of the crystal corresponding to the material through hole 2 is alleviated.
[0038] Experiment 5: This embodiment differs from Experiment 4 in that the skeleton structure material is composed of four stacked cylindrical material blocks 1, and the rest of the process is the same.
[0039] The AlN crystal grown in this embodiment has an overall growth rate of 80 um / h, and the surface of the crystal is overall flat.
[0040] Experiment 6: This embodiment differs from Experiment 5 in that the pore density of the cylindrical material block 1 decreases gradually from the central area to the edge area, and the rest of the process is the same.
[0041] The AlN crystal grown in this embodiment has an overall growth rate of 80 um / h, and the crystal surface is nearly flat and slightly convex.
[0042] Experiment 7: This embodiment differs from Experiment 5 in that the hole of the cylindrical material block 1 forms an angle of 60° with the surface, and the cylindrical material blocks 1 are stacked in the forward and reverse directions, as shown in the figure. The rest of the process is the same.
[0043] Compared with Experiment 6, there is no difference in the AlN crystals grown in this embodiment.
[0044] The advantages of Experiments 3 to 7 compared with Experiments 1 and 2 are mainly reflected in the following aspects: 1. Increased growth rate: In Experiment 3, by using a cylindrical material with uniformly distributed vertical through holes 2, the overall growth rate of the crystal was increased to 100 um / h, which was significantly improved compared to 50 um / h in Example 1 and 60 um / h in Example 2.
[0045] Although the growth rates of Experiments 4 to 7 were somewhat reduced, compared with Examples 1 and 2 which did not adopt special material structures, they still provided the possibility of optimizing the growth rate by adjusting the material structure.
[0046] 2. Improved crystal surface quality: In Experiment 3, although there is a concave phenomenon in the area of the crystal corresponding to the material through hole 2, this shows that the crystal growth morphology can be affected by adjusting the material structure.
[0047] In Experiment 4, by using a material with a skeleton structure and adjusting the position of through hole 2, the concave state of the crystal in the area corresponding to the through hole 2 of the material was alleviated.
[0048] Experiment 5 further achieved the overall flatness of the crystal surface by increasing the number of stacked cylindrical material blocks 1.
[0049] Experiments 6 and 7 further optimized the morphology of the crystal surface by more finely adjusting the pore density and the angle between the pores and the surface of the cylindrical material block 1, achieving a nearly flat and slightly convex shape.
[0050] 3. Provides more space for process adjustment: Experiments 3 through 7 employed different material structures, such as cylindrical materials with through-holes 2 and materials with skeleton structures, providing more flexibility in the AlN crystal growth process. This allows researchers to select the appropriate material structure to optimize the crystal growth process and final quality, depending on the application requirements and growth conditions.
[0051] In summary, compared with Experiments 1 and 2, Experiments 3 to 7 showed obvious advantages in increasing the growth rate, improving the crystal surface quality, and providing process adjustment space.
[0052] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent replacements and improvements made within the spirit and principles of the present application should be included in the scope of protection of the present application.
Claims
1. An AlN polycrystalline material with a skeleton structure, characterized in that: include: A plurality of cylindrical material blocks, each of which has a plurality of through holes formed in the axial direction; Furthermore, a plurality of cylindrical material blocks are stacked, and the through holes of the connected cylindrical material blocks are all connected.
2. The AlN polycrystalline material with a skeleton structure according to claim 1, wherein: The through holes are of any shape, and the number of the through holes is greater than or equal to three.
3. The AlN polycrystalline material with a skeleton structure according to claim 2, wherein: The radial cross-sectional area of the through hole is greater than or equal to 20 mm 2 .
4. The AlN polycrystalline material with a skeleton structure according to any one of claims 1 to 3, characterized in that: The through hole is arranged at an angle to the radial cross section of the cylindrical material block.
5. The AlN polycrystalline material with a skeleton structure according to claim 4, characterized in that: The angle range is set between 45° and 90°, and the directions of the through holes are all in the same direction.
6. The AlN polycrystalline material with a skeleton structure according to claim 5, characterized in that: When the angle is 90°, the connected cylindrical material pieces are stacked in an offset manner using the through holes.
7. The AlN polycrystalline material with a skeleton structure according to claim 5, characterized in that: When the angle is not 90°, the connected cylindrical material pieces are stacked upside down with their upper and lower surfaces reversed, so that the through holes form an "S"-shaped channel in the material.
8. A sintering device for sintering the cylindrical material block according to claim 7, characterized in that: include: A crucible bottom, wherein a plurality of rods are provided on the crucible bottom, and the rods are adapted to the through holes; A crucible wall is concentrically placed on the crucible bottom, and the thickness of the crucible wall is 1 to 3 mm; a crucible cover, concentrically placed on the crucible wall, wherein the diameter of the crucible cover is larger than the diameter of the crucible wall, and the diameter of the crucible cover is equal to the diameter of the crucible bottom; The inner side surface of the crucible cover abuts against the rod body.
9. A sintering device according to claim 8, characterized in that: The crucible bottom and the rod body are both made of tungsten material.
10. The sintering device according to claim 9, characterized in that: The crucible bottom and the crucible cover are both provided with right-angle chamfers, and the right-angle chamfers are used for mounting the crucible wall.